VERBAL BULLYING: COUNTERMEASURES AGAINST IN STUDENTS AT DARUL MUTTAQIEN ISLAMIC BOARDING SCHOOL - Muhammad Naelul Mubarok; Kama Abdul Hakam; Aceng Kosasih; Momod Abdul Somad (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This study aims to determine the efforts of the Darul Muttaqien Parung Islamic Boarding School in Bogor in overcoming verbal bullying that occurs among students. The type of research used in this study is field research. The method used in this study uses qualitative descriptive analysis methods. Data collection techniques are carried out by observation, interviews and documentation. The results of the study found that the management of verbal bullying in students at the Darul Muttaqien Parung Islamic Boarding School in Bogor was carried out by designing parenting regulations and strategies for overcoming verbal bullying. The countermeasures are arranged through a holistic/comprehensive parenting strategy in various elements of student life in the dormitory. These strategies are realized in a nurturing regulation. In its implementation, the countermeasures of verbal bullying are realized through preventive and also repressive strategies.